Social hegemony in contemporary India : in contemporary India - Thirunavukkarasu, R.(ed.) (New Delhi Sage, 2021)
"This edited book offers insights into the social inequalities that plague India and are often hidden behind terms like 'law and order' and 'constitutional democracy'. Though the market-driven economy was once expected to radically transform the heavily hierarchical Indian society into a more egalitarian order, the society remains unequal despite almost three decades of liberalization. Therefore, the liberal rhetoric of a democratic order and the free market guaranteeing social justice needs to be reappraised. Social Hegemony in Contemporary India demonstrates how socially privileged sections after acquiring and consolidating power at an alarming rate are now even more dominant over the lives of common Indians than at any time after 1947. Consequently, many communities-like Dalits and other neglected minorities-have been disempowered and pushed to the margins. Any resistance to the dominant social order and its status quo is punished through ostracization and violence. The mission for social justice, therefore, needs a fresh approach and actionable change from those who aspire for a truly liberated India, unshackled from inequity and bias"--
Keywords: Social conditions; Economic history